Family members' helping behavior: Alliance formations during naturalistic polyadic conflicts. Issue 4 (7th November 2016) - Persram, Ryan J.; Howe, Nina; Della Porta, Sandra; Ross, Hildy S.
Abstract: The present study investigated the role of alliances in naturalistic polyadic conflicts, which involved at least three family members, through a comparative analysis of parent–child‐ and sibling‐originated conflicts. Thirty‐nine families with two children (aged 4 and 6 years) were observed in the home setting. Transcripts of six 90‐min observational sessions per family resulted in identifying 306 polyadic family sequences; conflict initiators, topic, and resolution, as well as additional party roles (e.g., ally, judge, additional combatant, and mediator), were coded. Findings reveal that despite all family members being involved in polyadic conflicts, children tended to be initiators, while parents were more involved as additional parties. Alliances occurred more often than the other types of additional party roles. Alliance partnerships were most evident between mothers and fathers in parent–child‐originated conflicts, and mothers were more likely to ally with the younger child in sibling‐originated conflicts. Finally, submission was the most common resolution of polyadic conflicts; however, allies were more likely to win conflicts than to compromise or lose. This study highlights the dynamic nature of family conflict at home and is discussed in terms of links between relationships with family members, as well as informal learning of conflict behaviors. Highlights: Conflicts involving three or more family members occurs quite often at home. Alliances are a common role that family members assume in conflict, as they try to achieve a favourable outcome for their side. Children's involvement both as initiators and additional parties highlight their learning of various complex conflict behaviours in childhood.